Dokumenty synodów od 506 do 553 roku, (Synody i Kolekcje Praw, t. 8) układ i opracowanie A. Baron – H. Pietras SJ, ŹMT 73, Kraków 2014, Wydawnictwo WAM, ss. XXXVI + 763. - Szczur, Piotr (Vox Patrum, 2018)
nie dotyczy